2014
DOI: 10.1021/cg500560w
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Enhancement of Ezetimibe by a Cocrystal Engineering Technique

Abstract: The present study illustrates the formation and characterization of three different cocrystals of ezetimibe using methyl paraben as a coformer, employing three different processes, namely, solution crystallization, liquid assisted grinding, and reaction crystallization. Thermal analysis by differential scanning calorimetry (DSC) and thermogravimetric analysis were used as a primary analytical tool, followed by spectroscopic and crystallographic study as a confirmatory analytical tool. Equilibrium aqueous solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 38 publications
(66 reference statements)
0
39
0
Order By: Relevance
“…There was no correlation between melting point of cocrystal and API/coformer. The transformed melting points of cocrystals may be assigned to the physical non-covalent interaction between drug and coformer, altered packing arrangement or change in the crystallinity of molecules [31] .…”
Section: Resultsmentioning
confidence: 99%
“…There was no correlation between melting point of cocrystal and API/coformer. The transformed melting points of cocrystals may be assigned to the physical non-covalent interaction between drug and coformer, altered packing arrangement or change in the crystallinity of molecules [31] .…”
Section: Resultsmentioning
confidence: 99%
“…The experimentally determined temperatures and enthalpies of phase transitions observed on DSC curves are shown in Table 2. EZT and ASA show a characteristic single endotherm peak (ΔH = 106.7 J g −1 and ΔH = 176.5 J g −1 , respectively) [32] and aspirin (ΔH = 167.6 J g −1 , 141.0 °C) [33]. The DSC curves of the ASA-EZT mixtures clearly indicated that ASA and EZT formed a binary simple eutectic system.…”
Section: Phase Transition Studies In the Ezetimibe-aspirin Systemmentioning
confidence: 93%
“…The solid precipitates are also collected and analysed by HPLC to determine the stoichiometry of the complex. If the solid appeared to be a cocrystal based on the HPLC results, it is further characterized by DSC, TGA, and PXRD [84,100,101] .…”
Section: Solution-based Methodsmentioning
confidence: 99%